Effectiveness of COVID-19 Vaccines - Antonio, Nuno (2022)
Antonio, N., Rita, P., & Saraiva, P. (2022). Effectiveness of COVID-19 Vaccines: Evidence from the First-Year Rollout of Vaccination Programs. Vaccines, 10(3), 1-19. [409]. https://doi.org/10.3390/vaccines10030409 ---------------- The work by Nuno António, Paulo Rita, and Pedro Saraiva was supported by Fundação para a Ciência e a Tecnologia (FCT) within the Project: UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC).